PENGARUH KOMPETENSI DAN INDEPENDENSI AUDITOR DALAM PELAKSANAAN SHARIA COMPLIANCE DI LEMBAGA KEUANGAN SYARIAH (LKS) - Yunita Raj Alfan Putri; Nur Hidayati (Universitas Islam Malang, 2019)
ABSTRACT The purpose of this study was to determine the effect of auditor competency, and auditor independence in sharia compliance in Public Accountant Office (KAP) registered in Malang. This study uses a type of quantitative research. Sampling in this study used the convenience sampling method. The sampling technique is based on the availability of elements and the ease of obtaining them. So that a sample of 56 respondents was obtained. Data analysis in this study multiple linear regression models using SPSS. In this study it shows that the influence of independence of competencies affects sharia compliance. Based on the results of hypothesis testing, simultaneously showing that simultaneous Auditor Competence and Auditor Independence has an effect on Sharia Compliance (Sharia Compliance). Partially it shows that Auditor Competence and Auditor Independence affect Sharia Compliance (Sharia Compliance). In this study shows the competence and independence of auditors who apply simultaneously to sharia compliance.Keywords : Auditor Competency, Auditor Independence, Sharia Compliance